2016
DOI: 10.3102/0091732x16667700
|View full text |Cite
|
Sign up to set email alerts
|

Constructing and Reconstructing the “Rural School Problem”

Abstract: This chapter examines 100 years of rural education research in the context of the demographic, migratory, economic, and social changes that have affected rural America in the past century. The authors conducted a systematic review of the literature on rural teacher recruitment, retention, and training as a case study to examine the constancy and change in the construction of the “rural school problem,” a concept drawn from early work by urban education reformers. They found that attention to rurality as a fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 79 publications
(65 reference statements)
1
44
0
1
Order By: Relevance
“…This research commonly ignores, or mentions only in passing, the unique labor market challenges inherent in rural school systems. 3 Rural teacher labor markets have long been identified as an important area for research (Arnold et al, 2005;Harmon et al 2003; Programs for the Improvement of Practice, Office of Educational Research and Improvement, 1991;Stephens, 1985); there is some research evidence that rural schools have for decades faced particular challenges in adequately staffing classrooms (Azano et al, 2019;Biddle & Azano, 2016). Yet our understanding of rural school teacher labor markets is limited, which has led some to suggest that "to understand how appropriate and effective these or other [recruitment and retention] policies may prove to be, we must first develop a fuller understanding of the workings of rural teacher labor markets" (Miller, 2012a, p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…This research commonly ignores, or mentions only in passing, the unique labor market challenges inherent in rural school systems. 3 Rural teacher labor markets have long been identified as an important area for research (Arnold et al, 2005;Harmon et al 2003; Programs for the Improvement of Practice, Office of Educational Research and Improvement, 1991;Stephens, 1985); there is some research evidence that rural schools have for decades faced particular challenges in adequately staffing classrooms (Azano et al, 2019;Biddle & Azano, 2016). Yet our understanding of rural school teacher labor markets is limited, which has led some to suggest that "to understand how appropriate and effective these or other [recruitment and retention] policies may prove to be, we must first develop a fuller understanding of the workings of rural teacher labor markets" (Miller, 2012a, p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…For online courses, some estimates suggest that dropout may be 10% to 20% higher than in traditional face-to-face settings (de la Varre et al, 2014 [158]). Studies also highlight that educational benefits differ depending on students' characteristics, such as motivation, age and preparation (Ares Abalde, 2014 [1]; Bettinger and Loeb, 2017 [159]).…”
Section: Communications and Technologymentioning
confidence: 99%
“…Recent literature reviews of rural education research seek to change the narrative surrounding deficit perspectives of rural spaces and people. Biddle and Azano's (2016) historical review of rural teacher recruitment, retention, and training found that waves of education reform begat research that sought to solve the rural school problem. They contended that the construction of the rural school problem would be better supported by positioning research to seek out equity for rural spaces rather than pointing out rural problems and, thus, deficiencies.…”
Section: Response To Literature Reviewsmentioning
confidence: 99%
“…Beyond the rural theme, this issue is special for two related reasons. First, the articles that comprise this issue situate their studies within known gaps in the literature noted by recently published and forthcoming systematic literature reviews (Biddle & Azano, 2016;Burton, Brown, & Johnson, 2013;Their, Longhurst, Grant, & Hocking, 2019). Second, these articles present research that rejects deficit narratives of rural teaching.…”
Section: Flipping Narratives In New Spaces: An Introduction To Volumementioning
confidence: 99%